Mosquitoes (Diptera: Culicidae) in Eocene amber from the Rovno region, Ukraine - Giłka, Wojciech; Harbach, Ralph E.; Perkovsky, Evgeny E. (Zootaxa, 2021)
Culex ekaterinae sp. nov. is described based on an adult male embedded in amber from the Rovno region, northwestern Ukraine. The new species is compared with its presumed closest known relative, i.e. Culex erikae Szadziewski et Szadziewska, 1985 described from adults in Baltic amber. The two species exhibit distinct differences in the size of the main body parts, including the antenna, maxillary palpus and proboscis, as well as in the venation of the wing, the structure of the ungues and male genitalia—characters crucial in the diagnosis of adult mosquitoes. A redescription of Culiseta gedanica Szadziewski et Giłka, 2011, to date known from a single adult male, is presented based on a male in amber from Voronki, Rovno region. A tabulation of fossil Culicidae with their geological ages is provided.